Financial Integration in East Asia: An Empirical Investigation - Hyun-Hoo Lee; Hyeon-seung Huh; Donghyun Park (Asian Development Bank (ADB), 2011)
The central objective of this paper is to empirically evaluate the degree of linkages among East Asian equity and bond markets. The primary contribution of our paper to the empirical literature is that we use a financial gravity model grounded in economic theory. Using data from the International Monetary Fund's Coordinated Portfolio Investment Survey, we find that intra-East Asian financial asset holdings of four East Asian economies - Hong Kong, China; Japan; the Republic of Korea; and Singapore - are larger than the levels predicted by the financial gravity model. However, our analysis suggests that this result is likely to be driven by intraregional trade linkages, and reflects those linkages. Therefore, the salient implication for regional policy makers is that they should continue to promote intraregional financial integration. This paper also aims to analyze the impact of three different types of country-specific risks - political, economic, and financial risks - on investment from the four economies. This analysis yields a clear positive relationship between destination-country risk, particularly political risk and capital inflows.
hdl:11540/2039
Keywords: 330; Economic Development; Economic Infrastructure; Economic Policies; Regional Economic Development; Microfinance Programs; Public Finance; Finanzmarktregulierung; Rentenmarkt; Marktintegration; Gravitationsmodell; Hongkong; Japan; Südkorea; Singapur; Ostasien